PENERAPAN METODE LEAN SIX SIGMA DALAM MENINGKATKAN EFISIENSI PERKANTORAN PENDIDIKAN ISLAM - Yusuf, M. (ISLAMIC EDUCATION MANAGEMENT STUDY PROGRAM, 2023)
Abstract The efficiency of Islamic educational office is an important aspect in improving the quality of education. One method that can be applied is Lean Six Sigma, which focuses on waste elimination and process performance improvement. This study aims to analyze the implementation of Lean Six Sigma method in improving the efficiency of Islamic educational office. The focus of this research is to identify existing problems, design effective process improvements, and measure their impact on the efficiency of Islamic educational office. This research is based on literature review and relevant studies on the implementation of Lean Six Sigma in the context of education. Various relevant sources were utilized to gain a comprehensive understanding of the Lean Six Sigma concept and its implementation in Islamic educational office. The results of the study indicate that the implementation of Lean Six Sigma method can significantly improve the efficiency of Islamic educational office. In this research, the identified problems were successfully addressed through targeted process improvements and the use of Lean Six Sigma tools. The impact is evident in increased productivity, reduced waiting time, improved service quality, and cost savings. Keywords: lean six sigma, efficiency, Islamic educational office, service quality.